2023
DOI: 10.1177/00494755231157109
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in obstetrics: Hospital-based cohort study

Abstract: Obstetric acute kidney injury (AKI) is a serious unsolved global health-care problem and is a significant contributor to the overall burden of AKI resulting in devastating maternal and foetal outcomes. We studied the characteristics of obstetric AKI and the factors related to its unfavourable outcome. A total of 110 patients developed AKI among 10,138 admission giving a frequency of 1.08%. The commonest risk factor was pre-eclampsia followed by haemorrhage and sepsis. Complete recovery of renal function occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
3
3
0
Order By: Relevance
“…Our study showed a high rate of complete recovery of patients with PR-AKI (72.2%). This was higher than the Indian study in which about 50% of cases showed complete recovery [3] , and comparable to the 70.6% rate that was reported in the meta-analysis [29] , and to the 62.5% rate reported in the Egyptian study [28] .…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our study showed a high rate of complete recovery of patients with PR-AKI (72.2%). This was higher than the Indian study in which about 50% of cases showed complete recovery [3] , and comparable to the 70.6% rate that was reported in the meta-analysis [29] , and to the 62.5% rate reported in the Egyptian study [28] .…”
Section: Discussionsupporting
confidence: 76%
“…In our study, 10 cases (55.6%) needed dialysis while the rest of cases were managed without renal replacement therapy. This was higher than the Indian study in which only 26.4% of cases with PR-AKI needed dialysis [3] and comparable to the 55% rate that was reported in the meta-analysis including both hemodialysis and peritoneal dialysis [29] . The decision of dialysis was determined by nephrologist and ICU physician and followed the same indications in AKI that included presence of volume overload that is nonresponsive to diuretic therapy, presence of severe electrolyte and acid base abnormalities as persistent hyperkalemia refractory to medical treatment and presence of evident uremic manifestations as pericarditis or encephalopathy [24] .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations